2019
DOI: 10.1038/s41467-019-09641-9
|View full text |Cite
|
Sign up to set email alerts
|

Pellino1 regulates reversible ATM activation via NBS1 ubiquitination at DNA double-strand breaks

Abstract: DNA double-strand break (DSB) signaling and repair are critical for genome integrity. They rely on highly coordinated processes including posttranslational modifications of proteins. Here we show that Pellino1 (Peli1) is a DSB-responsive ubiquitin ligase required for the accumulation of DNA damage response proteins and efficient homologous recombination (HR) repair. Peli1 is activated by ATM-mediated phosphorylation. It is recruited to DSB sites in ATM- and γH2AX-dependent manners. Interaction of Peli1 with ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 60 publications
1
33
0
Order By: Relevance
“…The importance of UFMylation in ATM activation was also shown in another study by where they showed that UFL1 UFMylates meiotic recombination 11 (MRE11) at Lys 282, leading to MRN complex formation and ATM activation [25]. In the same context, showed that Pellino1, a ubiquitin ligase which responds to DNA DSBs, is involved in ATM activation through a phospho-H2AX-NBS1-ATM signaling axis [26]. These studies show that the mechanisms behind ATM activation are still being deciphered and suggest an important link to a wide range of post-translational modifications.…”
Section: Dna-pk) and (Chk1 Chk2): The Brotherhood Of Ddr Kinasesmentioning
confidence: 63%
“…The importance of UFMylation in ATM activation was also shown in another study by where they showed that UFL1 UFMylates meiotic recombination 11 (MRE11) at Lys 282, leading to MRN complex formation and ATM activation [25]. In the same context, showed that Pellino1, a ubiquitin ligase which responds to DNA DSBs, is involved in ATM activation through a phospho-H2AX-NBS1-ATM signaling axis [26]. These studies show that the mechanisms behind ATM activation are still being deciphered and suggest an important link to a wide range of post-translational modifications.…”
Section: Dna-pk) and (Chk1 Chk2): The Brotherhood Of Ddr Kinasesmentioning
confidence: 63%
“…Mammalian cells employ two major DNA repair pathways: homologous recombination (HR) and nonhomologous end-joining (NHEJ), to maintain cell survival [29][30][31]. Error-free HR repair requires a homologous template such as a sister chromatid, whereas NHEJ joins the two ends of a DSB through a process largely independent of homology [32]. Our previous research also showed that 500 µM VPA reduces HR e ciency [16], so we next explore whether 15 µM HPTA has the same effect on the frequency of HR in the above cell models.…”
Section: Hpta Results In the Accumulation Of More Dsbs In Response Tomentioning
confidence: 99%
“…In contrast, ATM responds to the generated DNA DSB throughout the cell cycle and promotes DSB repair. Following the detection of DNA DSBs, it has been reported that ATM is primarily activated by interacting with NBS1 from the MRN complex [107]. Oncogene activation and loss of G1 checkpoint control that drives cancer cell replication, leading to the cancer cell dependency on the S and G2/ M checkpoints and increased replication stress when cancer cells enter the S phase [108].…”
Section: Atr Mechanisms and Inhibitorsmentioning
confidence: 99%